2010
DOI: 10.1093/alcalc/agq076
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Affects the Late Differentiation of Progenitor B Cells

Abstract: Alcohol affects the ONP cell differentiation into B lineage at a late stage. Alcohol also down-regulates the expression level of TFs and cytokine receptors resulting in the impairment of B cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
1
12
0
3
Order By: Relevance
“…; Wang et al . ). However, to date, there are no studies about specific effects on different microflora components.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…; Wang et al . ). However, to date, there are no studies about specific effects on different microflora components.…”
Section: Resultsmentioning
confidence: 97%
“…The consumption of these stimulants, over a period of one or more decades has been shown to affect the integrity of the oral cavity and the local immune system (Malhotra et al 2010;Wang et al 2011). However, to date, there are no studies about specific effects on different microflora components.…”
Section: Oral Microbiota Is Modulated In a Species-specific Manner Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have found that EtOH consumption is associated with a lower production of B lymphocytes in the bone marrow (Chang et al, 2002;Wang et al, 2011), but this finding has not been confirmed by other groups (Cook et al, 2007;Zhang et al, 2012). In addition, excessive amounts of interleukin (IL) 4-a T helper (Th) 2 cytokine that prevails in ALD over the Th1 cytokines (Laso et al, 1999)-together with the inability of B cells to properly interact with IL-4, may also lead to an abnormally diminished B-cell expansion capacity, at least in patients with AH.…”
Section: Discussionmentioning
confidence: 99%
“…48,62 (43,98) 45,38 (42,38) 46,81 (46,20-49,01) 43,09 (36,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)29) р 0 = 0,032…”
Section: результаты и обсуждениеmentioning
confidence: 99%